Ordinary Women and Conservative Talk Radio in the US: A Comparative Study of Women Callers on The Rush Limbaugh Show and The Laura Ingraham Show (2004 -2010) - Sébastien Mort (European Journal of American Studies)
A phenomenon that emerged in the late 1980s under the aegis of Rush Limbaugh, conservative talk radio has played a major role in US politics. By offering a forum for the expression of conservative ideas which hitherto had been underrepresented in mainstream media, CTR has operated as a powerful instrument of dissent. However, the status of callers is problematic as the apparatus of these programs—such as the screening process or the host’s complete control over conservations—implies the violation of the criteria of authentic conversations. The caller’s status is even more problematic when callers are women: whether it deals with social or economic issues, CTR appears as an exclusive boys’ club. This article explores the status of women callers in comparative focus through a qualitative analysis of conversations between female callers and hosts on The Rush Limbaugh Show and The Laura Ingraham Show in 2004 and 2010. It shows that conversations on these two programs reveal a significant gender gap but argues that women’s contribution to the discussion is treated differently across programs: while Ingraham tends to offer women a more genuine opportunity to express themselves and treats them as equal partners in the conversation, Limbaugh instrumentalizes women’s contribution as part of his overall rhetorical strategy in order to advance conservatism, resorting to flattery and condescension. Ultimately, Limbaugh invites women’s participation mostly to reinforce the status quo of gender relationships, and thus appears as custodian of the traditional gender order. On the contrary, Ingraham recalibrates gender relationships in a way that is as favorable to women as it is to men, thus allowing conservatism to redefine its stance on gender equality.